Effect of gold nanoparticles on the performances of TiO2 dye-sensitised solar cell. Issue 6 (15th April 2018) - Liu, C.C.; Liang, M.S.; Khaw, C.C.
Abstract: TiO2 blended with Au nanoparticles (NP) was hydrothermally synthesised under controlled conditions and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). The dye-sensitised solar cells (DSSC) were characterized using the UV–vis spectrometry and current-voltage (I-V) testing. The performance of TiO2 -Au DSSC is significantly higher than TiO2 DSSC. The addition of Au NPs improves the light harvesting efficiency of the DSSC, thus improving the short circuit current density, J sc, and the conversion efficiency of the DSSC. The excitation of localised surface plasmon resonance of the Au nanoparticles utilised the strong local field enhancement around the Au NPs to increase the absorption in the surrounding TiO2 layer. It was demonstrated that the power conversion efficiency of the DSSC was improved by 28% with the addition of Au NPs.